Desenvolvimento de oócitos bovinos mantidos em líquido folicular - Lehmkuhl, Ricardo Coelho (2001)
To evaluate the effect of maintenance of bovine oocytes in follicular fluid (LF) for in vitro production of embryos, 1322 Complex Cumulus Oophorus (CCO's) obtained from abattoir bovine ovaries were distributed in two experiments. In the experiment I, maturation performed in TCM-199 for 24 hours (Control), was compared with the maintenance in follicular fluid at 30ºC for two (LF2), four (LF4) and six hours (LF6), followed by complementary TCM-199 maturation for 22, 20 and 18 hours, respectively. In the experiment II, oocyte maturation in TCM-199 for 24 hours (Control) and 18 hours (M18), was compared with the maintenance in LF for 6 hours followed by 18 hours TCM-199 maturation (LF6+M18). In both experiments, after maturation, the oocytes were transferred to Fert-Talp medium added of heparin and fertilization performed with semen selected by swim-up procedure. After that, zygotes were denuded and cultured in SOFaa medium. In the experiment I, the cleavage rate observed was 81.6% in Control group, 80.0% in LF2 group, 80.7% in LF4 group, and 81.7% in LF6 group. The blastocyst rate in D9 was 22.3%, 19.4%, 24.4% and 26.7% for Control group, LF2, LF4 and LF6 groups, respectively. No differences were observed (p>0.05). In experiment II, the cleavage rates (79.8%, 76.2% and 84.9%) and day 9 blastocyst rates (26.4%, 27.7% and 35.4%) in Control group, M18 and LF6+M18 groups, respectively, were not significantly different (p>0.05). The results obtained suggest that it is possible to maintain bovine oocytes in fluid obtained from follicles with 2 to 8mm of diameter, for periods until 6 hours at 30ºC, resulting in a simple, practical, and efficient alternative for maintenance and transport of bovine oocytes, for in vitro embryo production.